An assessment of human gastric fluid composition as a function of PPI usage. Issue 1 (27th January 2015) - Foltz, Emily; Azad, Sassan; Everett, Mary Lou; Holzknecht, Zoie E.; Sanders, Nathan L.; Thompson, J. Will; Dubois, Laura G.; Parker, William; Keshavjee, Shaf; Palmer, Scott M.; Davis, R. Duane; Lin, Shu S.
Abstract: The standard of care for chronic gastro‐esophageal reflux disease (GERD), which affects up to 40% of the population, is the use of drugs such as proton pump inhibitors (PPIs) that block the production of stomach acid. Despite widespread use, the effects of PPIs on gastric fluid remain poorly characterized. In this study, gastric fluid was collected from patients undergoing cardiac surgery who were not ( n = 40) or were ( n = 25) actively taking PPIs. Various enzymatic and immunoassays as well as mass spectrometry were utilized to analyze the concentrations of bile, gastricsin, trypsin, and pepsin in the gastric fluid. Proteomic analyses by mass spectrometry suggested that degradation of trypsin at low pH might account, at least in part, for the observation that patients taking PPIs have a greater likelihood of having high concentrations of trypsin in their gastric fluid. In general, the concentrations of all analytes evaluated varied over several orders of magnitude, covering a minimum of a 2000‐fold range (gastricsin) and a maximum of a 1 × 10 6 –fold range (trypsin). Furthermore, the concentrations of various analytes were poorly correlated with one another in the samples. For example, trypsin and bile concentrations showed a significant ( P < 0.0001) but not strong correlation ( r = 0.54). Finally, direct assessment of bacterial concentrations by flow cytometry revealed that PPIs did not cause a profound increase in microbial load in the gastric fluid. These results further delineate the profound effects that PPI usage has on the physiology of the stomach. Abstract : e12269 Further delineating the profound effects that PPI usage has on the physiology of the stomach, gastric fluid was collected from patients undergoing cardiac surgery who were not ( n = 40) or were ( n = 25) actively taking PPIs. Proteomic analyses by mass spectrometry suggested that degradation of trypsin at low pH might account, at least in part, for the observation that patients taking PPIs have a greater likelihood of having high concentrations of trypsin in their gastric fluid. Direct assessment of bacterial concentrations by flow cytometry revealed that PPIs did not cause a profound increase in microbial load in the gastric fluid, contrary with results previously obtained using culture‐dependent methods.